Application of DFT/TD-DFT Frameworks in the Drug Delivery Mechanism: Investigation of Chelated Bisphosphonate with Transition Metal Cations in Bone Treatment - Mollaamin, Fatemeh; Monajjemi, Majid (MDPI AG, 2023)
Carbon nanotubes (CNTs) are applied in a drug delivery system, which can be reacted with different structures such biomolecules. Bones have vital functions and are the locations of biochemical reactions in cells that might be exposed various diseases. As different metal ions are integral components of bone tissue with different functions in the physiological cellular medium as well as in bone treatment, they can be used differently as a basis or as a supplement for various materials in the field of bone repair. Therefore, this research aims to represent the recent progress in conjugated bisphosphonate (BP)-divalent transition metal ions of Mn2+, Fe2+, and Co2+ with an emphasis on the properties of interaction with a (6, 6) armchair carbon nanotube as a nanocarrier to exhibit the potential biomedical application of drug delivery. In this article, “CNT” linked to “BP“ of alendronic acid, ibandronic acid, neridronic acid, and pamidronic acid, which are chelated to transition metal cations of Mn2+, Fe2+, and Co2+, was investigated based on DFT insights for obtaining the electron charge density. Transition metals chelating with phosphonate groups, which are large with six O atoms with negative charges, are active in generating chelated complexes with the bisphosphonates [BPs- Mn2+/Fe2+/Co2+] through the status of drug design. In this work, B3LYP/6-311+G(d,p)/lanl2dz we have estimated the susceptibility of CNT for conjugating alendronic acid, ibandronic acid, neridronic acid, and pamidronic acid, which are chelated to transition metal cations of Mn2+, Fe2+, and Co2+ through NMR, NQR, IR, UV-VIS spectroscopy, and HOMO-LUMO analysis. Finally, the obtained results have confirmed that the possibility of applying CNT and BPs of alendronic acid, ibandronic acid, neridronic acid, and pamidronic acid becomes suitable in transition metal chelating for delivery application. The calculated HOMO–LUMO energy gaps for BPs of alendronic acid, ibandronic acid, neridronic acid, and pamidronic acid at the B3LYP/6-311+G (d,p) level have revealed that the energy gap reflects the chemical activity of the molecule.
Keywords: ibandronic acid; Chemistry; pamidronic acid; transition metal ion; nanocarrier; BPs; alendronic acid; neridronic acid; QD1-999; 3. Good health